TINJAUAN KONSEP PEDESTRIAN FRIENDLY DI LINGKUNGAN FAKULTAS TEKNIK UNIVERSITAS SRIWIJAYA - Dessy Syarlianti; Abdurrachman Arief (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title : Review of Pedestrian Friendly Concept in Engineering Faculty Area of Sriwijaya University The Engineering Faculty is part of Sriwijaya University Masterplan development scenario. The change of the vision and mission of the University has caused amendment to the activities, facilities and also the existing building structure. Pedestrian Friendly Concept is a concept that could answers common problems of the existing Engineering Faculty Design, such as the issue of sustainability, energy efficiency, as well as a re-attempt to humanize region-oriented vehicle. Orientation and arrangement of the siteplan should consider the human scale, especially for achievement within a campus. The purpose of this observation and analysis is to obtained several issues related to the implementation of the concept. Ends-mean method helps classify the existing problems so that it becomes a contextual pedestrian-friendly concept.